Carve the mark - Roth, Veronica (Roth, Veronica. Carve the mark, 2017)
Living on a violent planet where everyone develops a unique power meant to shape the future, Akos and Cyra, youths from enemy nations, resent gifts that render them vulnerable to others' control before they become unlikely survival partners.